A controllable and defectless cutting postprocess method via cleavage of an elastic cocrystal based on pyrene and tetrachloroterephthalonitrile. Issue 5 (20th January 2022) - Yu, Xu; Tang, Baolei; Zhang, Hongyu
Abstract : A controllable and defectless cutting postprocess method of an organic cocrystal based on pyrene and tetrachloroterephthalonitrile was proposed. The nature of that is revealed as cleavage, which shed light on the design of such materials. Abstract : An organic cocrystal based on pyrene and tetrachloroterephthalonitrile is reported in this work. The cocrystal exhibits both elastic and controllable and defectless cutting postprocess properties. The mechanism of postprocessing was studied via comparative study, nanoindentation and theoretical calculations in detail.